2006
DOI: 10.1016/j.cub.2006.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Endoplasmic Reticulum and mRNA Localization to the Yeast Bud

Abstract: Localization of messenger RNAs and local protein synthesis contribute to asymmetric protein distribution not only of cytoplasmic but also of membrane or secreted proteins. Since synthesis of the latter protein classes occurs at the rough endoplasmic reticulum (ER), mRNA localization and distribution of ER should be coordinated. However, this coordination is not yet understood. In yeast, mRNA localization to the growing bud depends on the myosin Myo4p, its adaptor She3p, and the specific RNA binding protein She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
134
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 29 publications
7
134
1
Order By: Relevance
“…6B, two Myo4p•She3p heterotrimers are proposed to be cross-linked by putative tER ligands into a transportcompetent motor complex. Coupling two Myo4p•She3p heterotrimers by either She2p•zipcode or tER ligand(s) may occur separately or in concert, in agreement with reported observations of discrete transport or cotransport of these two different cargos (29,32). Again, as for ASH1 mRNA, multiple ligands arranged consecutively along the surface of tubular ER could recruit multiple motor complexes, each consisting of two cross-linked Myo4p•She3p heterotrimers, yielding a more processive mode of transport in a millipede-like fashion.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…6B, two Myo4p•She3p heterotrimers are proposed to be cross-linked by putative tER ligands into a transportcompetent motor complex. Coupling two Myo4p•She3p heterotrimers by either She2p•zipcode or tER ligand(s) may occur separately or in concert, in agreement with reported observations of discrete transport or cotransport of these two different cargos (29,32). Again, as for ASH1 mRNA, multiple ligands arranged consecutively along the surface of tubular ER could recruit multiple motor complexes, each consisting of two cross-linked Myo4p•She3p heterotrimers, yielding a more processive mode of transport in a millipede-like fashion.…”
Section: Discussionsupporting
confidence: 90%
“…4D). We propose this highly conserved She3p coiled coil as a candidate binding site that represents the genetically mapped binding site on She3p for a hitherto unidentified ligand on the surface of tubular ER that can undergo transport from the mother to the daughter cell (28,32,39). As indicated in the model in Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Instead, cargo binds via an "adaptor" protein, swi5p-dependent HO expression 3 protein (She3p) (7). Notably, the 425-residue-long She3p contains at least four binding modules that appear to be sequentially arranged along its primary structure (8)(9)(10)(11). Our recent composite crystal structure of a region of She3p (comprising residues showed that two She3p molecules form a pseudocoiled coil (6).…”
mentioning
confidence: 99%
“…In this translocation complex, the myosin motor, termed Myo4p, interacts with the N-terminal half of its adapter protein She3p to translocate at least 26 different types of mRNA as well as endoplasmic reticulum (ER) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). For mRNA transport, the adapter protein She3p binds with its C-terminal half to the RNA-binding protein She2p (16,19,22,23).…”
mentioning
confidence: 99%